Natural selection shapes the evolution of SARS-CoV-2 Omicron in Bangladesh - Habib, Mohammad Tanbir; Rahman, Saikt; Afrad, Mokibul Hassan; Howlader, Arif Mahmud; Khan, Manjur Hossain; Khanam, Farhana; Alam, Ahmed Nawsher; Chowdhury, Emran Kabir; Rahman, Ziaur; Rahman, Mustafizur; Shirin, Tahmina; Qadri, Firdausi (Frontiers in Genetics, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has evolved to give rise highly transmissive and immune escaping variant of concern (VOC), known as Omicron. Many aspects of the SARS-CoV-2 evolution and the driving forces behind the on-going Omicron outbreaks remain unclear. Substitution at the receptor-binding domain (RBD) in the Spike protein is one of the primary strategies of SARS-CoV-2 Omicron to hinder recognition by host angiotensin-converting enzyme 2 (ACE2) receptor and avoid antibody-dependent defence activation. Here, we scanned for adaptive evolution within the SARS-CoV-2 Omicron genomes reported from Bangladesh in the public database GISAID (www.gisaid.org; dated April 2 nd , 2023). The ratio of non-synonymous (Ka) to synonymous (Ks) nucleotide substitution rate, also denote as ω, is an indicator of selection pressure acting on protein coding genes. Higher proportion of non-synonymous to synonymous substitutions (Ka/Ks or ω> 1) indicates positive selection, while Ka/Ks or ω near zero indicates purifying selection. Equal amount of non-synonymous and synonymous substitutions (Ka/Ks or ω = 1) refer to neutrally evolving sites. We found evidence of adaptive evolution within the Spike (S) gene of SARS-CoV-2 Omicron isolated from Bangladesh. In total, 22 codon sites of the S gene displayed signature of positive selection. The data also highlighted the receptor-binding motif (RBM) within the RBD of the Spike glycoprotein is a hotspot of adaptive evolution, where many of the codons had ω > 1. Some of these adaptive sites at the RBD of Spike protein are known to be associated with increased viral fitness. The M gene and the ORF6 have also experienced positive selection. These results suggest that although purifying selection has been the dominant evolutionary force, positive Darwinian selection also plays a vital role in shaping the evolution of SARS-CoV-2 Omicron in Bangladesh.